OPTIMIZING CYBERSECURITY PERFORMANCE: A PERFORMANCE-BASED ANALYSIS OF BLOCKCHAIN AND TRADITIONAL SECURITY ARCHITECTURES - Muhammad Moazam; Dr Jawaid Iqbal; Samarah Ashraf; Dr Mairaj Nabi (Spectrum of Engineering Sciences, 2025)
A quantitative benchmarking analysis of traditional versus blockchain-based cybersecurity solutions using a comparative holistic performance assessment approach was presented in this study. This research creates parallel testbeds where baseline security infrastructure consisting of a FortiGate firewall, Microsoft PKI, Splunk SIEM, and OpenVPN forms a traditional ecosystem, while Hyperledger Fabric, Ethereum, IPFS, and MetaMask set up the blockchain ecosystem. The evaluation encompassed latency (end-to-end transaction time), cost (3-year total cost of ownership), and attack resistance (threat simulated success rates). Six standardized test scenarios were conducted which included user login (10,000 simultaneous engagements), DDoS attack simulation (100Gbps), and logging (100,000 entries), with a 30 cycle test repetition for significant statistical confidence (ANOVA, α=0.05). Key trade-offs surfaced as findings blockchains showed commanding resistance to tampering with logs (0% alteration compared to 14.2% in traditional systems) while also possessing lower performance. Black systems exhibited higher latency (47.3seconds vs. 4.2 seconds for authentication) and 3-5x greater implementation costs. A hybrid decision framework developed from the research combines five performance dimensions: security, cost, speed, scalability, and compliance mapped to organizational profiles including SMB’s, enterprises and government, providing clear guidance for security architects. This research clarifies many of the operational claims and assumptions purported by the blockchain heralds, showcasing the practical realities applicable for modernization strategies in cybersecurity.